2015
DOI: 10.1177/1079063215618376
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Empirical and Clinical Support for Group Therapy Specific to Sexual Abusers

Abstract: This review compiles 48 empirical studies and 55 clinical/practice articles specific to group therapy with sex offenders. Historically, group therapy has always been the predominant modality in sex offender-specific treatment. In the first decades of the field, treatment applied a psychoanalytic methodology that, although not empirically supported, fully appreciated the primary therapeutic importance of the group modality. Conversely, since the early 1980s, treatment has applied a cognitive behavioral method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 77 publications
(115 reference statements)
0
11
0
3
Order By: Relevance
“…Some research (e.g.,Bernard et al, 2008; Burlingame, Fuhriman, & Johnson, 2002) characterizes group cohesion as analogous to the construct of therapeutic alliance in individual psychotherapy, which is widely recognized as essential to the process of change (Horvath & Luborsky, 1993; Weck, Grikscheit, Jakob, Hofling, & Stangier, 2014). Studies have demonstrated the benefits of cohesion in groups targeting individuals with alcohol use disorders (Osilla, Kulesza, & Miranda, 2017), early psychosis (Lecomte, Leclerc, & Wykes, 2017), anxiety disorders (Norton & Kazantzis, 2016), sexual abuse history (Jennings & Deming, 2015), binge-eating disorder (Gallagher et al, 2013), addiction (Ait-Daoud et al, 2006), social phobia (Taube-Schiff, Suvak, Antony, Bieling, & McCabe, 2007), and borderline personality disorder (Marziali, Munroe-Blum, & McCleary, 1997).…”
mentioning
confidence: 99%
“…Some research (e.g.,Bernard et al, 2008; Burlingame, Fuhriman, & Johnson, 2002) characterizes group cohesion as analogous to the construct of therapeutic alliance in individual psychotherapy, which is widely recognized as essential to the process of change (Horvath & Luborsky, 1993; Weck, Grikscheit, Jakob, Hofling, & Stangier, 2014). Studies have demonstrated the benefits of cohesion in groups targeting individuals with alcohol use disorders (Osilla, Kulesza, & Miranda, 2017), early psychosis (Lecomte, Leclerc, & Wykes, 2017), anxiety disorders (Norton & Kazantzis, 2016), sexual abuse history (Jennings & Deming, 2015), binge-eating disorder (Gallagher et al, 2013), addiction (Ait-Daoud et al, 2006), social phobia (Taube-Schiff, Suvak, Antony, Bieling, & McCabe, 2007), and borderline personality disorder (Marziali, Munroe-Blum, & McCleary, 1997).…”
mentioning
confidence: 99%
“…Overall, sex offenders typically prefer group therapy over individual therapy, but both have been found to be equally effective (Aparicio, ; Jennings & Deming, ). Notably, a meta‐analysis found that individuals in group therapy had the lowest sexual recidivism rates when compared with mixed group and individual treatment (Gannon, Oliver, Mallion, & James, ).…”
Section: Treatment Studiesmentioning
confidence: 99%
“…Generally, groups should foster an environment of strong cohesion and aim to achieve greater interpersonal learning effects (Jennings & Deming, 2017;Lampalzer & Briken, 2019;Levenson, Prescott, & D'Amora, 2010;Willemsen et al, 2016). Jennings and Deming (2013) suggest using operant conditioning in group psychotherapy to reinforce social interaction and bonding.…”
Section: Group Psychotherapymentioning
confidence: 99%
“…There is strong evidence of a moderate relationship between group cohesion and outcome in group therapy (16). Empirical findings on Yalom's generic factors in group therapy for sex offenders were compiled in a review article (17).…”
Section: Therapeutic Factors and Micro-processes In Therapymentioning
confidence: 99%